Habit of cooking pork on hot stones as main risk of cysticercosis - Sandy, Semuel; Oktavian, Antonius; Kawulur, Hanna S; Widiyanti, Mirna; Sasto, Iman HS; Maladan, Yustinus (Faculty of Medicine, Trisakti University, 2018)
BackgroundCysticercosis is an infectious disease caused by the larval form of Taenia solium (cysticercus cellulosae) and has been ranked as the most important food-borne parasite of humans in terms of public health, socioeconomic and trade impact. Cysticercosis is still a health problem in Papua and is inseparable from socio-cultural factors, hygiene and environmental sanitation. The aim of this study was to investigate the seroprevalence of cysticercosis and the risk factors that contribute to cysticercosis.MethodsA cross-sectional study was conducted in March-November 2016 involving 800 subjects. Demographic data and risk factors were collected using questionnaires. Cysticercosis serological examination was performed by means of the magnetic microsphere bead immunoassay technique coupled with rT24H recombinant protein to detect serum rT24H cysticercosis specific antibodies. The data obtained were analyzed by bivariate test (chi-square) and logistic regression.ResultsCysticercosis seroprevalence in Papua was 3.6% (284/7 874). The logistic regression analysis found that the risk factors playing the role of predictor were cooking pork with hot stones [OR=3.06; 95%CI: 2.19-4.28; p=0.000], nail hygiene [OR=2.05; 95%CI: 1.57-2.67; p=0.000], consumption of raw vegetables or salads [OR=0.52; 95%CI: 0.30-0.91; p=0.022], use of river water for washing foods [OR= 1.92; 95%CI: 1.39-2.64; p=0.000].ConclusionsCooking pork with hot stones was the main risk factor of cysticercosis. Suspected cases of T. solium in pigs should be confirmed by molecular methods. Both taeniasis and human cysticercosis should be notifiable and surveillance in animals should be improved.